America. - Dower, John, fl. 1838-1846?
This map shows most of the Western Hemisphere, including North and Central America, South America, and the surrounding oceans and islands. Countries are outlined using various colors. Cities, bodies of water, and geographic features are marked (with relief shown by hachures). Scale [ca. 1:42,240,000].